Innovative Media Applications in Facilitating Arabic Language Learning for Students in Madrasah - Rizqoh, Jazilatur; Taufik (Academia Publication, 2024)
Arabic is a must for Muslims. Arabic is currently the international language of Saudi Arabia. Learning Arabic is also a native language or a foreign language that is often heard. Learning Arabic requires a learning medium. Arabic learning media is currently evolving and adapting to the increasingly sophisticated technological revolution. Learning media plays a vital role in the success of teaching and learning activities. Just like today's app media, there are many teachers who can easily use innovative apps using their mobile phones. The use of media is a teaching skill of teachers in the classroom. There are four skills to master Arabic in MI/SD: listening, speaking, reading and writing skills.These skills can be easily mastered if teachers use media as a learning aid. The data collection methodology used by the library through processing, analysis and summarization of the data obtained.The aim of the study is to examine what is meant by innovative media such as media in Arabic language learning and the use of media in Arabic language learning.